Living traditions - Glassie, Henry, 1941-; Mahmud, Firoz, 1943-; Asiatic Society of Bangladesh; Cultural Survey of Bangladesh Project (Dhaka : Asiatic Society of Bangladesh, 2007)
Contributed articles published under the Cultural Survey of Bangladesh Project; translated from Bengali; chiefly on the handicrafts and traditional arts of Bangladesh.
Includes bibliographical references and index.
00026336
Keywords: Material culture -- Bangladesh; Decorative arts -- Bangladesh